Coś w zamian za uśmiech. (Gdynia : [s.n.], 1948)
Afisz inf. o występie zespołu "Awangarda" 13.03.1948 r. w gdyńskiej kawiarnii Patria.
Keywords: Kawiarnie -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Życie muzyczne -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne